The accuracy and responsiveness of continuous noninvasive arterial pressure during rapid ventricular pacing for transcatheter aortic valve replacement - Schramm, Christoph; Huber, Anja; Plaschke, Konstanze (Anesthesia & analgesia, 2013)
Background: The accuracy of measurement of the continuous noninvasive arterial blood pressure (CNAP) technique is unknown during sudden cardiocirculatory arrest. - Methods: In 33 patients undergoing elective transfemoral aortic valve implantation procedures under analgesic sedation, invasive arterial blood pressure (IAP) was compared with a CNAP device during episodes of severe hypotension (functional cardiocirculatory arrests by rapid pacing) and the remaining time without severe hypotension. Systolic, diastolic, and mean pairs of blood pressure measurements were extracted for both groups and were analyzed by Bland-Altman plots. The responsiveness of the CNAP technique was assessed in the various phases of severe hypotension concerning time and amplitude of changes. - Results: Overall CNAP accuracy (bias), calculated by subtracting IAP from CNAP, was −6.3 ± 18.9, 7.4 ± 10.5, and 4.0 ± 11.3 mm Hg (mean ± SD, systolic, diastolic, and mean). Bias increased during episodes of severe hypotension to 11.8 ± 14.5, 13.8 ± 12.4, and 12.9 ± 12.4 mm Hg. The percentage of agreements (95% confidence interval) between the blood pressure pairs with a difference ≤15 mm Hg was 58.5% (57.9-58.6), 75.8% (75.5-76.0), 82.2% (81.9-82.4; systolic, diastolic, mean) for all data and 56.4% (54.2-58.9; P = 0.71), 53.2%* (51.1-56.0), and 57.4%* (56.3-59.1; *P < 0.001) during rapid pacing. The responsiveness of mean CNAP and mean IAP did not differ significantly during the various phases of rapid pacing. - Conclusions: The stand-alone CNAP monitor (model 500at, software V3.5) accurately and rapidly measures the changes of blood pressure that occur during sudden development of cardiocirculatory arrest and recovery to baseline blood pressures. CNAP monitors the duration of the arrest.
Gesehen am 19.07.2021